Społeczna szkodliwość czynu jako określenie zła w polskim prawie karnym? - Doroszewska, Katarzyna ("Młody Jurysta" Czasopismo Studentów i Doktorantów Wydziału Prawa i Administracji UKSW, 2017)
Most people associate crime with conduct considered as an “evil” or “bad”. But in Polish Criminal Code there is no such word as „evil”. Can it lead to the conclusion that law is ethically neutral? Or there is other factor, which can be acknowledged as synonym? The only clause that could be associated with the “evil” is the clause of “social harm”, which is used as one of the statutory elements of the crime. Prima facie the meaning of this clause is clear, but in a specific case, the distinction between minor and significant social harm can be very hard. The aim of this clause is to differ acts that can be acknowledged as crime or minor offense. But isn’t the real meaning of social harm an attempt to differ between the “good” and “bad” conducts? The doctrine vary in describing the nuances of the issue taking into consideration different element of the act. Nearly everybody agrees that the real value of harm which was done is not important. The main problem discussed in the article is the meaning of social harm as the aspect of „evil”. In fact, the law cannot have neutrally attitude to crime. Essential aspect of criminal law is to criticize harmful acts and Polish law does it by using “the social harm” clause. The question is what is considered evil in Polish law and what kind of factors determine it?